Clinical characteristics and outcomes of children with WAGR syndrome and Wilms tumor and/or nephroblastomatosis: The 30-year SIOP-RTSG experience - Hol, JA (2021)
Background: WAGR syndrome (Wilms tumor, aniridia, genitourinary anomalies, and range of developmental delays) is a rare contiguous gene deletion syndrome with a 45% to 60% risk of developing Wilms tumor (WT). Currently, surveillance and treatment recommendations are based on limited evidence. Methods: Clinical characteristics, treatments, and outcomes were analyzed for patients with WAGR and WT/nephroblastomatosis who were identified through International Society of Pediatric Oncology Renal Tumor Study Group (SIOP-RTSG) registries and the SIOP-RTSG network (1989-2019). Events were defined as relapse, metachronous tumors, or death. Results: Forty-three patients were identified. The median age at WT/nephroblastomatosis diagnosis was 22 months (range, 6-44 months). The overall stage was available for 40 patients, including 15 (37.5%) with bilateral disease and none with metastatic disease. Histology was available for 42 patients; 6 nephroblastomatosis without further WT and 36 WT, including 19 stromal WT (52.8%), 12 mixed WT (33.3%), 1 regressive WT (2.8%) and 2 other/indeterminable WT (5.6%). Blastemal type WT occurred in 2 patients (5.6%) after prolonged treatment for nephroblastomatosis; anaplasia was not reported. Nephrogenic rests were present in 78.9%. Among patients with WT, the 5-year event-free survival rate was 84.3% (95% confidence interval, 72.4%-98.1%), and the overall survival rate was 91.2% (95% confidence interval, 82.1%-100%). Events (n = 6) did not include relapse, but contralateral tumor development (n = 3) occurred up to 7 years after the initial diagnosis, and 3 deaths were related to hepatotoxicity (n = 2) and obstructive ileus (n = 1). Conclusions: Patients with WAGR have a high rate of bilateral disease and no metastatic or anaplastic tumors. Although they can be treated according to existing WT protocols, intensive monitoring of toxicity and surveillance of the remaining kidney(s) are advised.